SH005S7 Overcomes Primary and Acquired Resistance of Non-Small Cell Lung Cancer by Combined MET/EGFR/HER3 Inhibition. (15th September 2022) - Kang, Sooyeon; Kim, Ji Hye; Hong, Jisoo; Moon, Ji Hong; Kwon, Yun Young; Ko, Seong-Gyu
Abstract : In this study, we have examined the anticancer effects of SH005S7 on MET-amplified and (HCC827GR) NSCLC cells and their primary HCC827 cells. In vitro, first of all, cell viability and colony formation assay confirmed the growth inhibitory effects of SH005S7 on both cells. Second, SH005S7 inactivated EGFR-related multiple cell signaling, which was associated with a marked decrease in the constitutive phosphorylation of EGFR, HER3, MET, AKT, and ERK. Third, SH005S7 attenuated the anchorage-independent cell growth. Fourth, SH005S7 blocked invasive and metastatic capability by downregulation of mesenchymal markers—vimentin, snail, and MMP-9. Fifth, BrdU assay confirmed the cell cycle arrest of SH005S7 on these cells. When administered orally to nude mice xenografically transplanted human NSCLC, SH005S7 inhibited the growth of tumor and did not cause hepatotoxicity and nephrotoxicity in animals. Immunohistochemical and Western blot analyses of tissue showed that the suppression of growth correlated with inhibition of proliferation (Ki-67, PCNA), invasiveness (vimentin, snail), and angiogenesis (CD31) marker and decrement in the constitutive and phosphorylation of EGFR, HER3, MET, AKT, and ERK. Additionally, SH005S7 had immune stimulatory effects by TNF- α cytokine release on macrophage, without cell cytotoxicity. Overall, our results suggest that SH005S7 can inhibit the growth of MET-amplified and gefitinib-resistant NSCLC cells through the suppression of EGFR-related multiple targets linked to overcome gefitinib resistance.